The origins of the Sardinian Parliament in a European context. (4th May 2019) - Blockmans, Wim; Galoppini, Laura
ABSTRACT: The recent publication of two volumes of the acts of the Sardinian Parliament, edited by Laura Galoppini, offers an opportunity to pay attention to this extraordinary rich documentation now covering a continuous period of 175 years. In 1355 King Pedro IV of Aragon convened a first assembly, modelled on the Aragonese corts . The second meeting, in 1421, aimed at the completion of the island's conquest and the financing of that conquest. It was only since the 1480s that regular meetings took place, albeit it that their convening was determined by the royal need for subsidies. The remarkably long negotiations on the estates' petitions and complaints reveal new insights into the island's social tensions and economic problems, and its role in the struggle for domination in the Western Mediterranean.